INTERPERSONAL DIALOGUE TO BUILD STUDENTS’ ABILITY IN USING ENGLISH - Nurul Hidayati (STBA Pontianak, 2020)
This study aims to see the implementation of interpersonal dialogue in learning English to enhance students' ability in using the English language. This study used a qualitative method. The data collection technique uses observation techniques to see the process of the implementation of learning to use interpersonal dialogue, and interview techniques to determine the impact of implementing interpersonal dialogue. Respondents in this study were lecturer and students. The results showed that during the learning process, the interpersonal dialogue was created between students and students and lecturer. Then, there is an increase in learning activities, student participation, students get additional knowledge in the form of vocabulary, grammar, pronunciation, and self-confidence. In conclusion, the implementation of interpersonal dialogue can build communicative learning, because of the interactive communication between students and lecturers, as well as students and students during the learning process. As well as increasing student ability and student confidence in using English.